Electrochemical Behaviour of 3,4-Dichlorobenzophenone Oxime - Suresh Reddy, C.; Jayarama Reddy, S. (Asian Journal of Chemistry, 2010)
The electrochemical reduction behaviour of 3,4-dichlorobenzophenone oxime has been studied in different supporting electrolytes covering a pH range from 2.0 to 12.0 in methanol-water mixtures by employing d.c. polarography, cyclic voltammetry, millicoulometry and controlled potential electrolysis. The kinetic parameters such as diffusion coefficient (D) and heterogeneous forward rate constant (kof, h) values were evaluated and reported. A reduction mechanism is proposed in consistence with the data obtained.